Initial teacher training in Brazil and Portugal: a qualitative investigation in times of pandemic (Práxis Educativa, 2024)
This article aims to presents results obtained in the study on teacher training policies and the challenges and learning that impacted the initial training paths of future teachers during the pandemic caused by the COVID-19 and the methodological paths that responded to the formative expectations of that period. The research context took place in initial teacher training courses at the Distance Education Center of the State University of Santa Catarina (UDESC), Brazil, and the Department of Education and Psychology of the University of Aveiro, Portugal. This is qualitative, exploratory, multiple case study type research. The research corpus consisted of documentary sources from both countries and interviews under the content analysis. The webQDA software was used to process and analyze the data, with multiple variables for classification, articulation and triangulation with different data sources. The study showed that this period, in addition to being challenging for teacher training, brought new practices and learning in relation to the context of supervised curricular internship, as the “new normal” is still a path under construction, but that could be the point departure for new investigations and inquiries as the adjustments caused by the pandemic are consolidated.Keywords: Initial teacher training. COVID-19 pandemic. Supervised curricular internship.